Design of Learning Media for the Application of Electronic Circuits - Syahroni Zikri Aulia; Thamrin Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
In the era of the Industrial Revolution 4.0, the use of technology in education has become essential for enhancing the quality of learning. One of the challenges in teaching the subject of Applied Electronics Techniques in vocational schools is students' difficulty in understanding abstract concepts, particularly those related to Field Effect Transistors. This study aims to develop and evaluate an animation-based learning media using Blender software to improve students' comprehension. The research method employed is the 4D model (Define, Design, Develop, Disseminate). Validation was conducted by media and subject matter experts, while practicality testing was carried out by 11th-grade students at SMK Negeri 1 Padang. The validation results indicate that this learning media is highly valid, with an average score of 95% from subject matter experts and 90% from media experts. The practicality test conducted by students yielded a score of 92.10%, indicating that the media is highly practical for learning. The conclusion of this study is that Blender-based animated videos are effective as learning media to help students understand the concept of Field Effect Transistors. This media can enhance students' learning motivation and engagement in the learning process.